PEMBUATAN ARANG 4 JENIS BAMBU DENGAN CARA TIMBUN - Tjutju Nurhayati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
A study on charcoal manufacture using pit method was carried out 4 bamboo species from West Java, namely andong (Gigantochloa verticillata Munro), ater (Gigantochloa ater Kurz), bitung (Dendrocalamus asper Back) and tali (Giganiochloa apus Kurz). The charcoal produced which was completed after 2 days, were then subjected to chemical analysis. The analysis consist of specific gravity, moisture content, ash, volatile matter and fixed carbon. In addition to the aboue test, the charcoal of each species were tested in blacksmith which manufacture chopping knife.The result shows that out of the 4 bamboo species tested, ater seems to be the best with regard to charcoal yield, chemical properties and application in blacksmith work.